2015
DOI: 10.1002/hed.24249
|View full text |Cite
|
Sign up to set email alerts
|

Valid and reliable techniques for measuring fibrosis in patients with head and neck cancer postradiotherapy: A systematic review

Abstract: To date, there are no valid and reliable techniques for measuring fibrosis postradiotherapy for head and neck cancer, especially within the suprahyoid and pharyngeal regions. © 2015 Wiley Periodicals, Inc. Head Neck 38: E2322-E2334, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 130 publications
0
13
0
Order By: Relevance
“…For these studies, it is important to be able to select potential patients in an early stage. Treatment options like stretching exercises and prophylactic swallowing exercises are very time-consuming and less likely to be used on the long term in a less than average compliant population [9]. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For these studies, it is important to be able to select potential patients in an early stage. Treatment options like stretching exercises and prophylactic swallowing exercises are very time-consuming and less likely to be used on the long term in a less than average compliant population [9]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these techniques have shown a clear benefit up to now [9]. Since the treatment options for fibrosis following RT for HNC are limited, we must currently focus on prevention.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, nearly all previous treatments will increase the difficulties in detecting LN recurrence in the treated neck of patients with head and neck cancers. The preceding radiation will lead to fibrotic tissue changes in the treated neck 3 . Preceding surgery such as neck dissection or flap reconstruction will cause anatomic variations in the treated neck.…”
Section: Introductionmentioning
confidence: 99%
“…Acute injuries resolve within a few weeks post radiation therapy, however subacute and late term injuries take time to develop and may lead to chronic impairments (King, Dunlap, Tennant, & Pitts, 2016;Naoko Saito, 2012). Long-term changes may be associated with persistent oxidative damages that have been shown to be a key characteristic in radiation injury (Shaw, Skoretz, O'Sullivan, Hope, Liu, & Martino, 2016). In the head and neck muscles, previous reports using MRI have demonstrated that radiation can result in fibrosis in pharyngeal constrictors as seen by significant increase in tissue inflammation and edema 3-months post radiation (Popovtzer, Cao, Feng, & Eisbruch, 2009).…”
Section: Radiation Injurymentioning
confidence: 99%